Catalog of the types of Curculionoidea (Insecta, Coleoptera) deposited at the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”, Buenos Aires - Bachmann, Axel Oscar (2013)
The type specimens of Curculionoidea (Apionidae, Brentidae, Anhribidae, Curculionidae, Platypodidae, and Scolytidae) from the Museo Argentino de Ciencias Naturales (MACN), corresponding to all current categories, are herein catalogued. A total of 344 specific and subspecific names are alphabetically recorded, for their original binomina or trinomina, and spellings. Later combinations and synonyms are mentioned, as well as the information of all the labels associated to the specimens. In order to assist future research, three further lists are added: 1. specimens deemed to be deposited at MACN but not found in the collection; 2. specimens labeled as types of species which descriptions have probably never been published (non available names); and 3. specimens of dubious type status, because the information on the labels does not agree with that of the original publication.